Disruptive frugal digital innovation in Africa - Nyagadza, Brighton; Bashar, Abu (Emerald Publishing Limited, 2025)
Informed by the 2030 Agenda for Sustainable Development and Sustainable Development Goals (SDGs) framework - emphasising fostering sustainable economic growth and higher gross domestic product growth per annum in the least developed countries - Disruptive Frugal Digital Innovation in Africa provides the reader with theoretically informed and practically grounded solutions to addressing sustainable development for humans. Taking a multi-faceted approach, the readers of this edited volume gain insights into the role of disruptive frugal technological innovation and transformative futures in Africa. Considering macro, meso, and firm-level analyses relating to how disruptive frugal technological innovation and transformative futures, Disruptive Frugal Digital Innovation in Africa proposes implementations towards positive development in under-researched African contexts. Each chapter provides theoretical, policy and practical implications for policy makers, educational practitioners, students and business communities on how disruptive frugal technological innovation and transformative futures strategies could be of benefit to them.